2018
DOI: 10.4172/2155-9546.1000545
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Ghanas Aquaculture Industry

Abstract: Globally, the aquaculture industry has seen significant development through increased fish production, as a result of increased demand for fish and fish products. Ghana's aquaculture sector has seen significant growth in recent years, due to the government/World Bank-funded fisheries program through Ministry of Fisheries and Aquaculture Development (MOFAD). The national aquaculture production grew from over 32,512 MT/y in 2013 to 52,470.49 MT/y, representing 11.3% of the national harvest, in 2016. Aquaculture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…In Africa, cage aquaculture is growing rapidly in natural and man‐made lakes (Musinguzi et al, 2019), in many cases prompted by a decline in capture fisheries (Cowx & Ogutu‐Owhayo, 2019; Temesgen et al, 2019). Volta Lake in Ghana, West Africa, is one of the world's largest man‐made lakes, and although primarily created for hydroelectric power generation, aquaculture has become an important economic activity (Amenyogbe et al, 2018). A key objective of the Ghana National Aquaculture Development Plan is to increase output from aquaculture to make up for the short fall in domestic supply from capture fisheries (Fisheries Commission, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, cage aquaculture is growing rapidly in natural and man‐made lakes (Musinguzi et al, 2019), in many cases prompted by a decline in capture fisheries (Cowx & Ogutu‐Owhayo, 2019; Temesgen et al, 2019). Volta Lake in Ghana, West Africa, is one of the world's largest man‐made lakes, and although primarily created for hydroelectric power generation, aquaculture has become an important economic activity (Amenyogbe et al, 2018). A key objective of the Ghana National Aquaculture Development Plan is to increase output from aquaculture to make up for the short fall in domestic supply from capture fisheries (Fisheries Commission, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Fish farming is also progressively gaining grounds in contributing to the domestic market. However, farmed fish is relatively expensive and may be unaffordable to poor consumers [6]. Quagrainie and Chu [1] revealed that the poor are known to depend largely on low-priced small pelagic fish species, such as sardines and mackerel, which are processed in a variety of ways (dried, smoked, fried, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Aquaculture feed forms about 60% of production costs increasing the overall production cost and thereby reducing the profit margins of the regular aquaculture activities as compared to the wastewater fed aquaculture (Hasan, 2007). With fish feed being the most expensive component in traditional fish culture (Amenyogbe et al, 2018) taking that aspect out in wastewater fed aquaculture makes it a more affordable method of fish production. This indicates that wastewater fed aquaculture has the potential to be more economically successful as compared to regular aquaculture assuming high survival rates and good growth rates are achieved.…”
Section: Cost Benefit Analysismentioning
confidence: 99%
“…The aquaculture sector is a very important sector in the country's development contributing about 3-5% to the country's GDP. Apart from augmenting the shortage in the quantity of fish demanded relative to the fish supplied, the industry provides a source of livelihood to about 10% of Ghana's population (Amenyogbe et al, 2018). Wastewater fed aquaculture is becoming an attractive alternative to mainstream aquaculture because of the low capital investment.…”
Section: Cost Benefit Analysismentioning
confidence: 99%